SCHOOL TEACHER OUTSIDE OF CLASS: SELF-REFLECTION OF PEDAGOGUES FROM LATVIA AND RUSSIA ON THEIR COOPERATION WITH COLLEAGUES - Jermolajeva, Jelena; Bogdanova, Tatiana; Silchenkova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In this article teachers’ self-reflection on the cooperation with colleagues is considered. In the study the instruments elaborated in the framework of Latvian-Russian research project on modern teacher professional identity (2014 – 2018) were used: the six component model of the content of the teacher professional identity and the questionnaire “School Teacher Professional Identity”. In the international survey carried out in 2017 schoolteachers from Latvia and the Smolensk region of Russia participated; the total number of respondents was 437. The aim of the article is to analyze and compare the data of two national samples for the items of the questionnaire concerning the teachers’ self-reflection on the cooperation with colleagues, and reveal differences in views and attitudes of the urban and rural teachers from Latvia and Russia. In general, the mentioned items have relatively high scores in both national samples. At the same time certain differences between the data of Latvian and Russian respondents as well as the urban and rural subgroups of both countries are observed.